IMPACT OF ILLNESS PERCEPTION AND COPING STRATEGIES ON QUALITY OF LIFE AMONG MIGRAINEURS - Bibi, Humaira; Naz, Summaira; Khan, Mussarat Jabeen (Pakistan Armed Forces Medical Journal, 2021)
Objectives: To find out the impact of illness perception and coping strategies on quality of life among migraineurs. Study Design: Correlational study. Place and Duration of Study: The sample was selected from different hospitals of Hazara Division, from Mar to Jul 2018. Methodology: The sample of 300 migraineurs with age range 18-55 years was selected from hospitals of Hazara Division through purposive sampling technique. Brief illness perception questionnaire, The World Health Organization Quality of Life Scale (WHOQOL-BREF) and brief cope scale were used for data collection. Results: Illness perception significantly predicted (p=0.002) quality of life in positive direction. The results also explored that positive coping (p≤0.001) and problem focused coping strategies (p=0.002) predict quality of life significantly positively; whereas active avoidance coping strategies (p≤0.001) significantly negative predict quality of life; while religious denial coping was non-significant predictor of quality of life. Conclusion: Illness perception has significant negative relationship with quality of life, problem-focus coping (PFC), and positive coping (PC). Illness perception has significant positive relationship with religious denial coping (RDC) and active avoidance coping (AAC).